Analysis of Socio-emotional Development in Mathematics Learning Through Multi-representative Based Test Instruments: Analysis of Socio-emotional Development in Mathematics Learning Through Multi-representative Based Test Instruments - Nisa Iftita Maharani, Nisa Iftita Maharani (Jurnal Riset Pendidikan Matematika Jakarta, 2024)
This article examines social-emotional development in mathematics learning through a systematic literature review. The formulation of the problem in this study is as follows: How does the development of social-emotional awareness in literature take place? What are the students' social-emotional characteristics? What difficulties might students with low social-emotional levels encounter when learning math? context for observing students' social-emotional development. The results of this study show that social-emotional development in literature achieves students' social-emotional development in learning, specifically students show attitudes of interest, participation, and communication. Communication, interaction, ability to work in groups and independently. confidence, but the points he has not achieved are calmness, difficulty adapting, privacy and difficulty communicating with people he considers strangers. Achieve students' social-emotional development outside of school hours, i.e. students show empathy, care, help friends, are not selfish and know how to control emotions when interacting and having fun , while what hasn't been achieved is just playing with close friends , less achieved. Pay attention to what's going on around you, speak only when necessary, and prefer learning to playing.